Contribution of inline skating to learning basics of alpine skiing - Igor Božić; Vjekoslav Cigrovski; Goran Bošnjak; Vladimir Jakovljević; Gorana Tešanović (University of Banja Luka, Faculty of physical education and sport, 2017)
Aim of this research was to determine contribution of inline skating to learning basics of alpine skiing. We included 139 participants, who were attributed to two groups - control and experimental. Participants of the experimental group (n=72) were included in 10-days program of learning inline skating while participants pertaining to control group (n=67) did not participate in any kind of sport or recreational program. Before and after inline skating, all participants were tested on six elements of alpine ski technique. Participants of the experimental group had better results on elements of alpine ski technique (4.09 vs. 3.29; p=0.00). Our results suggest inline skating aids better learning of alpine skiing.